2013
DOI: 10.1128/genomea.00107-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the First Aichi Virus Isolated in Taiwan

Abstract: The first Aichi virus (AiV), kvgh99012632/2010, was identified in Taiwan. The entire genome of the AiV isolate was sequenced and compared to known AiV sequences. Genome alignment revealed that the Taiwan AiV strain shares 96.3% nucleotide and 99% amino acid identities with the German strain D/VI2287/2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…A nucleotide difference of ≈20% from the available sequences of genotypes A, B, and C was observed, tentatively leading to the conclusion that this sequence might belong to a new genotype of Aichi virus. More sequence information is needed to substantiate this finding by isolating this Aichi virus strain and subsequently subjecting the virus to whole-genome sequencing, as was described for an Aichi virus isolated in Taiwan in 2010 ( 36 ). For 3 of the sewage water concentrates from our study, 3C sequences were detected that showed high similarities with the recently discovered canine kobuvirus ( 37 , 38 ) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…A nucleotide difference of ≈20% from the available sequences of genotypes A, B, and C was observed, tentatively leading to the conclusion that this sequence might belong to a new genotype of Aichi virus. More sequence information is needed to substantiate this finding by isolating this Aichi virus strain and subsequently subjecting the virus to whole-genome sequencing, as was described for an Aichi virus isolated in Taiwan in 2010 ( 36 ). For 3 of the sewage water concentrates from our study, 3C sequences were detected that showed high similarities with the recently discovered canine kobuvirus ( 37 , 38 ) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Among those, two complete genome sequences of T. phaeum [ 9 ], “T. acetatoxydans” [ 10 ] and one draft genome sequence of C. ultunense [ 11 ] have been published, the later two by this working group. Here, we are presenting the draft genome sequence of the third mesophilic SAOB Syntrophaceticus schinkii strain Sp3.…”
Section: Introductionmentioning
confidence: 99%
“…The human AiV, genome accession no. JX56424 25 , was isolated from a newborn with diarrhea in Taiwan and propagated in Vero cells (ATCC: CCL-81, Manassas, VA, USA). Human lung carcinoma A549 cells (ATCC: CCL-185) and HEK293T cells (ATCC: CRL-3216) were cultured in Dulbecco's Modified Eagle Medium (DMEM) with 10% fetal bovine serum (FBS) and 100 μg/ml penicillin/streptomycin (Gibco, ThermoFisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%